Self-Actualization of the Main Characters in Ford County, by Grisham - Dhina Melinda; Emzir Emzir; Sabarti Akhadiah (STKIP Singkawang, 2019)
This research aimed to obtain a deep depiction of self-actualization on the main character in Ford County the stories written by Grisham This research is a study of the psychology of literature, which is analyzed objectively by using the psychological theory of humanistic. The research refers to the combination between motivation theory of Maslow especially in Hierarchy of human needs and the concept of self-actualization by Rogers. In data analysis techniques, qualitative data in the form of expressions, utterances and occasions are needed through the content analysis method and analyzed through a structural literature approach based on the concept of literary theory. The focus of the study is self-actualization of the main characters, which can be observed from the seven short stories of Ford County. The focus of the study then would be divided into sub-focuses, which tends to the hierarchy of human needs, they are physiological needs, safety needs, love needs, self-esteem needs, and self-actualization needs. Another sub-focus is the concept of self-actualization’s achievement in forms of openness for experience, personal existence, strong belief, freedom, and creativity. The result of the research indicates that the main characters of the stories like Rogers, in Blood Drive, and Mack in Fish Files have D-Motivation in their Self-Actualization. Then the main characters of the stories like Raymond in Fetching Raymond, Sidney in Casino, Stanley in Michael Room, Gilbert in Quite Heaven and in Adrian Funny Boy, reflects B-Motivation in their own self-actualization.